Placing Technology - Yuk Hui; Samuel Koh; Dulmini Perera (Footprint)
In this interview, the editors met with Professor Yuk Hui, the originator of the notion of cosmotechnics, to discuss the implications of cosmotechnical thinking for architecture, urbanism and design. While Hui's work contains strong implications for architecture and spatial disciplines, he has rarely addressed them directly. In this far-ranging discussion, Hui brings together diverse topics, including the philosophy of Lewis Mumford, the cross-cultural history of cybernetics, and technology's connection to sacred space.